2009
DOI: 10.1093/sleep/32.12.1559
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Contribution to Motor Memory Consolidation: A Motor Imagery Study

Abstract: These results provide evidence that sleep contributes to the consolidation of motor sequence learning acquired through MI and further suggests that offline delayed gains are not related to the MI content per se. They extend our previous findings and strongly confirm that performance enhancement following MI is sleep dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 34 publications
10
33
0
Order By: Relevance
“…In line with previous studies showing a motor performance enhancement following the same amount of either physical or mental training (Debarnot et al, 2009a;Feltz & Landers, 1983;Guillot & Collet, 2008), compared to a lack of practice (Debarnot et al, 2011b), we found that all participants improved motor learning performance through MI training both in terms of speed and accuracy of the FTT. Furthermore, and in keeping with previous results (Debarnot et al, 2009a(Debarnot et al, ,b, 2011b, similar sleep-related effects were seen following MI practice, while the simple passage of time was not sufficient to provide additional benefits.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with previous studies showing a motor performance enhancement following the same amount of either physical or mental training (Debarnot et al, 2009a;Feltz & Landers, 1983;Guillot & Collet, 2008), compared to a lack of practice (Debarnot et al, 2011b), we found that all participants improved motor learning performance through MI training both in terms of speed and accuracy of the FTT. Furthermore, and in keeping with previous results (Debarnot et al, 2009a(Debarnot et al, ,b, 2011b, similar sleep-related effects were seen following MI practice, while the simple passage of time was not sufficient to provide additional benefits.…”
Section: Discussionsupporting
confidence: 92%
“…There is now ample evidence that MI and physical practice share several characteristics at temporal, behavioral and neural levels (Holmes & Collins, 2001;Munzert, Lorey, & Zentgraf, 2009). Practically, similar performance gains have been observed after a night of sleep when participants practiced MI compared to physical practice of an explicit FTT, while a comparable time interval during daytime did not affect motor memory consolidation (Debarnot, Castellani, Valenza, Sebastiani, & Guillot, 2011a;Debarnot et al, 2009a). These results further reinforced the principle of functional equivalence between MI and physical practice, by demonstrating sleep related effects on motor memory consolidation following MI.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Accordingly, the participants subjected to PP and MI training took less time to perform the pursuing tracking task after practice. These results are consistent with those of the motor learning literature, which have extensively demonstrated the effectiveness of MI in improving the spatiotemporal and dynamic control of motor performance (Gentili, Papaxanthis, & Pozzo, 2006;Papadelis et al, 2007;Yágüez, Nagel, Hoffman, Canavan, Wist, & Hömberg, 1998;Debarnot, Creveaux, Collet, Doyon, & Guillot, 2009;Debarnot, Creveaux, Collet, Gemignani, Massarelli, Doyon, & Guillot, 2009). …”
Section: Discussionsupporting
confidence: 90%
“…The participants subjected to a nap reduced the time needed to complete the sequence from the posttraining test to the retest, while those from the rest control groups showed a decrease in performance of motor memory consolidation in the same way as after physical practice and to identify which sleep stage might primarily mediate this consolidation process. Previous research provided strong evidence that performance enhancement following MI is sleep dependent and that the simple passage of time is not sufficient to provide additional benefits in participants who are not subjected to sleep (Debarnot et al, 2009b;Debarnot et al, 2010). Combined with the latter results, and most especially to the fact that the participants who did not perform MI practice did not improve their motor performance, the present findings showed that a daytime nap after MI practice improved motor performance and, therefore, facilitated motor memory consolidation, as compared to spending a similar time interval in the rest state.…”
Section: Mean Movement Times (S)mentioning
confidence: 99%